Crenobiont, stygophile and stygobiont molluscs in the hydrographic area of the Trebišnjica River Basin - Andrzej Falniowski; Brian Lewarne; Aleksandra Rysiewska; Artur Osikowski; Sebastian Hofman (ZooKeys, 2021)
In the paper the crenobiont, stygophile and stygobiont malacofauna of the karst area of Popovo Polje around Trebinje (Eastern Herzegovina, BiH) is presented. The materials were collected from springs, caves and interstitial habitats (with a Bou-Rouch pump) at 23 localities. The following species were found: Pisidium cf. personatum A.W. Malm, 1855, Theodoxus callosus (Deshayes, 1833), Sadleriana fluminensis (Küster, 1852), Radomaniola curta (Küster, 1852), Radomaniola cf. bosniaca (Radoman, 1973), Kerkia briani Rysiewska & Osikowski, 2020, Montenegrospeum bogici (Pešić & Glöer, 2012), Litthabitella chilodia (Westerlund, 1886), Travunijana vruljakensis Grego & Glöer, 2019, a new genus and species of the Sadlerianinae, Emmericia ventricosa Brusina, 1870, Iglica cf. absoloni (A.J. Wagner, 1914), Plagigeyeria tribunicae Schütt, 1963, Paladilhiopsis arion Rysiewska & Osikowski, 2021, Valvata montenegrina Glöer & Pešić, 2008, Radix labiata (Rossmässler, 1835), Galba truncatula (O. F. Müller, 1774), Ancylus recurvus Martens, 1783, Ancylus sp. and the amphibiotic Succinea cf. putris (Linnaeus, 1758). The redescription of the genus Travunijana Grego & Glöer, 2019, applying the characteristics of shell, female reproductive organs and penis, is also presented. The new genus and species are described, based on the shell, penis, radula and fragmentary data on the female reproductive organs. For all species, the mitochondrial cytochrome oxidase subunit I (COI) is applied to confirm the determination; in the case of Travunijana and the new genus, the nuclear histone H3 locus is also used, in order to infer both their distinctiveness and phylogenetic relationships.